TINJAUAN SISTEMATIS: STRATEGIS SCAFFOLDING PADA PEMBELAJARAN MATEMATIKA - Kusmaryono, Imam; Wijayanti, Dyana (Phenomenon : Jurnal Pendidikan MIPA, 2020)
This scientific article presents the results of a literature review on scaffolding strategies in mathematics education (2015-2020). The literature review was based on 32 scientific publications that met the inclusion criteria and were included in the final analysis with a total sample size of 1368 students (participants). In theory, this literature research aims to provide an empirical picture of the latest literature on the application of scaffolding strategies and analyze teacher-student interaction patterns when scaffolding is implemented in mathematics learning. The results of this literature review indicate that the pattern of teacher-student interaction when scaffolding support follows an approach: one-to-one scaffolding, peer-scaffolding, and computer-based scaffolding. here are three categories of teacher tendencies in providing scaffolding support, Â namely: cognitive scaffolding, affective scaffolding, and metacognitive scaffolding. The results of the literature review also concluded that the application of scaffolding strategies in mathematics learning was effective in terms of reducing mathematics anxiety, motivating and increasing student achievement